Neue Befunde zur Pluralität der Lebensformen - Wagner, Michael; Franzmann, Gabriele; Stauder, Johannes (Zeitschrift für Familienforschung, 2001)
Although family sociologists have intensely discussed the diversification of living arrangements for a long time, there is still insufficient knowledge about the extent to which this process has actually taken place. This paper examines the diversity of living arrangements in three steps: first, a chronological documentation of the diversification of living arrangements in Germany; secondly a description of cohort differentiation; and thirdly, a comparison with other European countries. Results indicate only a very slight diversification between 1971 and 1999. There are significant changes of diversity within cohorts along the age axis, but not between cohorts. Finally, the diversity of living arrangements in Germany is shown to be near the European average.